American College of Rheumatology Guidance for COVID‐19 Vaccination in Patients With Rheumatic and Musculoskeletal Diseases: Version 1. Issue 7 (24th May 2021) - Curtis, Jeffrey R.; Johnson, Sindhu R.; Anthony, Donald D.; Arasaratnam, Reuben J.; Baden, Lindsey R.; Bass, Anne R.; Calabrese, Cassandra; Gravallese, Ellen M.; Harpaz, Rafael; Sadun, Rebecca E.; Turner, Amy S.; Williams, Eleanor Anderson; et al.
Abstract : Objective: To provide guidance to rheumatology providers on the use of coronavirus disease 2019 (COVID‐19) vaccines for patients with rheumatic and musculoskeletal diseases (RMDs). Methods: A task force was assembled that included 9 rheumatologists/immunologists, 2 infectious disease specialists, and 2 public health physicians. After agreeing on scoping questions, an evidence report was created that summarized the published literature and publicly available data regarding COVID‐19 vaccine efficacy and safety, as well as literature for other vaccines in RMD patients. Task force members rated their agreement with draft consensus statements on a 9‐point numerical scoring system, using a modified Delphi process and the RAND/University of California Los Angeles Appropriateness Method, with refinement and iteration over 2 sessions. Consensus was determined based on the distribution of ratings. Results: Despite a paucity of direct evidence, 74 draft guidance statements were developed by the task force and agreed upon with consensus to provide guidance for use of the COVID‐19 vaccines in RMD patients and to offer recommendations regarding the use and timing of immunomodulatory therapies around the time of vaccination. Conclusion: These guidance statements, made in the context of limited clinical data, are intended to provide direction to rheumatology health care providers on how to best use COVID‐19 vaccines and to facilitate implementation of vaccination strategies for RMD patients.